FORENSIK BIOLOGI DALAM PENJAGAAN NASAB (HIFZ AL-NASAB / NASL)(FORENSIC BIOLOGY IN PRESERVATION OF LINEAGE/ANCESTRY (HIFZ AL-NASAB / NASL)) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
Maqasid al-Shari'ah focusses on each of the elements in al-Daruriyyāt, followed by al-Hajiyyat and al-Tahsiniyyāt. Among the main topics in the discussion of al-Daruriyyāt is Hifz al-Nasl/ Nasb which is the preservation of ancestry. It is admitted that forensic science provides a consistent role in human life. However, only few know the success of forensic science in solving great significance cases in determining the lineage that led to one of the key elements of al-Daruriyyāt in Maqasid al-Shari'ah. Therefore, this study aimed at investigating the role of forensic science in determining the heredity. This study has the objective to analyze the classic texts which contain elements of forensic science that led to the determination of lineage, to review the appropriate techniques in determining heredity and analyse relevant cases in determination of heredity proven by forensic science. Method used is this study were historical, inductive and deductive. Scope of the study were the determination of heredity through physical trait analysis and serology (blood) in cases which are not related to Islamic criminal jurisprudence. This study concluded that the forensic biology is an accurate method in preserving heredity and it is in line with the Islamic legal maxims.
Keywords: Blood serology; Hifz al-Nasl / nasb; al-Qiyafah; al-Qarinah; Physical Trait; biological forensic